WAYS TO INCREASE INVESTMENT EFFICIENCY IN ENSURING REGIONAL COMPETITIVENESS (Marketing Journal, 2025)
This article discusses the need to increase investment efficie ncy in ensuring regional competitiveness, its specific and most important features, existing opportunities and ways to increase efficiency. Conclusions and proposals are made to increase this efficiency.
Keywords: region; competitiveness; investment; efficiency; competition; regional competitiveness